Respon pertumbuhan dan hasil tanaman Kacang Tanah terhadap perbedaan dosis pupuk kotoran Sapi - Baso Daeng; Liz Yanti Andriyani; Yaved Muyan; John Payai (Agrotek, 2022)
The domestic peanut production, which continues to increase along with the increase in human population, requires the need for peanut commodities to be assisted by procurement from abroad. This is exacerbated by the growing challenges and obstacles faced in agriculture in general. The narrowing availability of agricultural land and the phenomenon of declining soil productivity lead farmers to innovate through an organic farming approach. Cow manure is a reliable potential organic fertilizer as a solution to solve the problems faced. The study aimed to see the response shown in the growth component and yield of peanut plants due to the application of cow dung fertilizer with different dosage. The results of the study showed that the difference in the dose of cow dung fertilizer had an unreal influence on the growth component and the component of peanut yield. However, it can be seen that the tendency of a dosage of cow dung fertilizer of 30 tons per hectare to provide better results.